Tanatopolítica y control social : la violencia como dinamizador del orden y la limpieza social en Bucaramanga, Colombia (1988-1998) - Álvaro Acevedo Tarazona; Andrés Correa Lugos (Amnis)
At the end of the 20th century, Colombia saw an exponential growth in violence as a result of the boom in drug trafficking and the internal armed conflict. Faced with this situation, alternatives were implemented to exercise social control, such as states of exception and other non-legal forms of repression, which were mainly exercised by informal actors who, with the support of the Military Forces, administered the ways of dying at their will. and to kill. This article analyzes the violent and illegal forms of social control implemented in the city of Bucaramanga (Colombia) between the years of 1988 and 1998 by paramilitary groups such as « La Mano Negra ». These forms of social control by paramilitary actors provoked a privatization of justice and influenced the discredit and trust of citizens in the face of the institutions.